THE RELEVANCE OF IMPLEMENTING THE DISCIPLINES OF PROJECT GRAPHICS AND ERGONOMICS IN THE PROFESSIONAL TRAINING OF ENVIRONMENTAL DESIGNERS - Gnatiuk, Liliia; Novik, Hanna; Pylypenko, Nataliia (Theory and practice of design, 2025)
The article analyzes contemporary design education programs in Ukraine and abroad. The place and role of project graphics and ergonomics in shaping the professional competence of environmental designers are identified. The advantages of an interdisciplinary approach are summarized. Recommendations for updating curricula are proposed. A comparative analysis of curricula in Ukrainian and international institutions has been conducted. The results of a pedagogical experiment on the implementation of these disciplines in the educational process are generalized. The significance of project graphics and ergonomics in the development of professional competencies is revealed, highlighting their function as a universal language of professional communication in the field of design. These disciplines perform both a technical role (accurate representation of design ideas) and a conceptual one (conveying the project’s style, mood, and ideology). The purpose of the study is to justify the relevance and necessity of introducing the disciplines «Project Graphics and Ergonomics» into the professional training of environmental designers in higher education institutions, as well as to identify effective ways to integrate these disciplines into the educational process. Methodology. The study employs theoretical research methods, systems analysis, and synthesis of existing domestic and international literature, specialized publications, and the practical experience of teaching professional-cycle disciplines. Results. The research established that the disciplines «Project Graphics and Ergonomics» are critically important for shaping the professional identity of environmental designers. Their integration into educational programs ensures not only technical proficiency but also the development of humanistic, ethical, and aesthetic dimensions of design thinking. The implementation of these disciplines contributes to a holistic understanding of the environment. Project graphics develop visual thinking and communication skills, while ergonomics focuses on user-centered design and enhances quality of life through design solutions. It is recommended to revise educational programs to include the synergistic study of both disciplines. Further research should focus on developing modular courses and integrated learning environments using digital technologies. Scientific novelty lies in the substantiation of the necessity to integrate these disciplines as a mandatory component of professional design training, in order to align educational programs with modern labor market demands, technological advancements, and the principles of human-centered design. Practical relevance is reflected in the development of a unified approach to implementing the «Project Graphics and Ergonomics» course in the curricula of higher education institutions, and in the need to study its impact on educational outcomes and its further integration into design-related disciplines.